Kesetiaan Seorang Perempuan: Analisis Kitab Rut - Ascteria Paya Rombe (Institut Agama Kristen Negeri Toraja, 2020)
Abstract: The Book of Ruth is one of the Old Testament books that is classified as a book of history. The story in the book of Ruth took place during the reign of the judges. The time when the apostasy of the nation of Israel was so apparent. The time when the Israelites began to worship idols. A time when there was competition among the tribes of Israel. The book of Ruth begins with famine in the land of Israel, which brought the family of Elimelech from Bethlehem-Judah to migrate to the land of Moab and settled there. The story continues with a sad story. Naomi's husband and even her two children died in the land of Moab. The series of stories left the impression that there was no presence of God in the midst of the Naomi family. Resulting in two widows who finally struggled to survive. Through literature study, two main points from the series of stories are revealed. First, even though God seems invisible, but behind everything God does not stop nurturing. God is present in silence. God works through the lives of faithful people. Second, despite the various crises that hit the country, even though evil and sin continue to be made by humans, even though it is as if God left humanity. But truly God is still the Alpha and Omega, who will not leave the deeds of his hands but always and always work in the midst of humanity who hope, loyal, and surrender to Him. Keywords: Naomi, Ruth, Nurturing, Loyalty, God Abstrak-Kitab Rut merupakan salah-satu dari Kitab Perjanjian Lama yang tergolong sebagai kitab sejarah. Kisah dalam kitab Rut terjadi pada zaman pemerintahan hakim-hakim. Masa di mana kemurtadan bangsa Israel begitu nampak. Masa di mana bangsa Israel mulai menyembah berhala. Masa di mana terjadi persaingan di antara suku Israel. Kitab Rut di awali dengan kelaparan di tanah Israel, yang membawa keluarga Elimelekh dari Betlehem-Yehuda merantau ke tanah Moab dan menetap di sana. Kisahnya terus berlanjut dengan kisah yang menyedihkan. Suami Naomi bahkan kedua anaknya meninggal di tanah Moab. Rentetan kisahnya meninggalkan kesan tiada kehadiran Allah di tengah-tengah keluarga Naomi. Mengakibatkan dua orang janda yang akhirnya berjuang untuk dapat bertahan hidup. Melalui studi kepustakaan tersingkap dua hal pokok dari rentetan kisah tersebut. Pertama, sekalipun Allah seolah-olah tidak nampak namun di balik semuanya Allah tidak berhenti memelihara. Allah hadir dalam kesenyapan. Allah berkarya melalui hidup orang yang setia. Kedua, Meskipun berbagai krisis melanda negeri, meskipun kejahatan dan dosa terus diperbuat manusia, meskipun seakan-akan Allah meninggalkan umat manusia. Namun sungguh Allah tetaplah Alfa dan Omega, yang tidak akan meninggalkan perbuatan tangannya melainkan selalu dan senantiasa berkarya di tengah-tengah umat manusia yang berharap, setia, dan berserah kepada-Nya. Kata Kunci: Naomi, Rut, Memelihara, Kesetiaan, Allah